Profiling fragments for carotenoid esters in Penaeus monodon by ultra‐high‐performance liquid chromatography/quadrupole‐Orbitrap high‐resolution mass spectrometry. (16th October 2020) - Li, Shuang; Fang, Keyi; Chen, Shubing; Xu, Jilin; Chen, Juanjuan; Chen, Haimin
Abstract : Rationale: The precise identification of carotenoid esters of Penaeus monodon, especially those in the carotenoid skeleton, needs to occur during mass spectrometry analysis. Detailed structural information about carotenoid esters is significant not only for the assessment of nutritional quality, but also for tracing biosynthetic precursors. Methods: The profiling of carotenoid esters in P. monodon was elucidated using ultra‐high‐performance liquid chromatography coupled with quadrupole‐Orbitrap high‐resolution mass spectrometry (UHPLC/Q‐Orbitrap‐HRMS). The raw LC/MS data were analyzed using Exact Finder™ software. Results: The structurally relevant ions, *l and *m, were considered markers of the astaxanthin monoester. Moreover, the carotenoid skeleton was unequivocally identified using the diagnostic ions *i, *j / *j' and *g / *g' generated by the carbon–carbon bond cleavage between β‐ionone ketones and conjugated polyene moieties. In total, 24 carotenoid esters were identified in P. monodon based on the fragmentation patterns discussed above. The identified carotenoid skeleton includes astaxanthin, astacene, oxidized astaxanthin and adonixanthin, which have been described for the first time. Conclusions: Characterization of the unknown carotenoid esters demonstrates the capabilities of this methodology, which is significant for enriching the carotenoid species in P. monodon .